International benchmarking in type 1 diabetes: Large difference in childhood HbA1c between eight high‐income countries but similar rise during adolescence—A quality registry study. Issue 4 (14th April 2020) - Anderzén, Johan; Hermann, Julia M.; Samuelsson, Ulf; Charalampopoulos, Dimitrios; Svensson, Jannet; Skrivarhaug, Torild; Fröhlich‐Reiterer, Elke; Maahs, David M.; Akesson, Karin; Kapellen, Thomas; Fritsch, Maria; Birkebæk, Niels H.; et al.
Abstract: Objectives: To identify differences and similarities in HbA1c levels and patterns regarding age and gender in eight high‐income countries. Subjects: 66 071 children and adolescents below18 years of age with type 1 diabetes for at least 3 months and at least one HbA1c measurement during the study period. Methods: Pediatric Diabetes Quality Registry data from Austria, Denmark, England, Germany, Norway, Sweden, the United States, and Wales were collected between 2013 and 2014. HbA1c, gender, age, and duration were used in the analysis. Results: Distribution of gender and age groups was similar in the eight participating countries. The mean HbA1c varied from 60 to 73 mmol/mol (7.6%‐8.8%) between the countries. The increase in HbA1c between the youngest (0‐9 years) to the oldest (15‐17 years) age group was close to 8 mmol/mol (0.7%) in all countries ( P  < .001). Females had a 1 mmol/mol (0.1%) higher mean HbA1c than boys ( P  < .001) in seven out of eight countries. Conclusions: In spite of large differences in the mean HbA1c between countries, a remarkable similarity in the increase of HbA1c from childhood to adolescence was found.